Analisis Proyeksi Pertumbuhan Penduduk Terhadap Kondisi Ketenaga Kerjaan di Kecamatan Simo - Keishya Humaira Zulfa (JURNAL PENDIDIKAN DAN ILMU SOSIAL (JUPENDIS), 2024)
Population growth in Simo District has experienced a significant increase in the last few years. Analysis of population projections on employment conditions in Simo District is very important to know the direction of economic development in Simo District. In this study, an arithmetic formula was used to calculate population projections because it has the highest accuracy by assuming that the population in the future will increase by the same amount every year. Based on calculations using arithmetic formulas, the following are the results of population projections for 2020-2040 in Simo District. In recent years, Simo District has experienced significant population growth, which has the potential to affect employment conditions in the area. Therefore, analysis of population growth projections on employment conditions in Simo District is very important to know the direction of economic development in Simo District.